Sentence Fragments in Major US Network News Broadcasts: The Nightly News on ABC, CBS, and NBC - Bosch, James Vanden (Stylistyka, 2006)
In this paper, I report on the follow-up to my earlier work on assessing the uses of sentence fragments in the nightly news programs o f the major US television networks. In that earlier work (“Stylistika” XI [2002], pp. 315-323), I had called attention to the very high incidence of sentence fragments, and of a particular kind of fragment, in the NBC ne[1]wscasts. That particular kind of fragment is very similar grammatically to the absolute phrase (AKA absolute clause), and such fragments made up nearly half of the fragments in the transcripts I studied. In this follow-up report, I have studied the newscasts of the other two major news networks in the US -ABC and CBS-during the same time period, November 29-December 1,2000. As I report here, it turns out that the preference for the absolute phrase fragment style o f NBC almost certainly constitutes a house style; the transcripts of the ABC and CBS broadcasts are not nearly as rich in fragments as the NBC transcripts are. In this report I have also attempted to show the extent to which certain newsmen and women have used or not used such constructions in these broadcasts